Developing mentors: an analysis of shared mentoring practices - Bower-Phipps, Laura; Klecka, Cari Van Senus; Sature, Amanda L (The New Educator, 2016)
Understanding how experienced teachers share and articulate effective mentoring practices can guide efforts to prepare quality mentors. This qualitative study focused on mentoring practices within a teacher-designed student-teaching program conceptualized while the mentor teachers within the program were students in a graduate-level mentoring course and implemented upon the mentors’ completion of their graduate studies. Data sources included interviews and field notes from meetings with mentors and student teachers. The results detail specific mentoring practices: explicit instruction through scaffolding, developing the whole teacher, student-teacher-directed learning, fostering student teachers’ individual practice, explicit mentoring of one another, and reflecting on mentoring. These practices were enabled by program structures such as mentor meetings, an online forum, and mentors’ observation of all student teachers in the program. © 2016, © 2016 CCNY and ATE.
Keywords: dept.cur; peer-reviewed